CORRELAÇÃO ENTRE PARÂMETROS BIOMÉTRICOS E PRODUTIVOS EM COLÔNIAS DE Melipona quadrifasciata anthidioides LEPELETIER (HYMENOPTERA: APIDAE) - Patricia Faquinello (Ciência Animal Brasileira, 2013)
In meliponini colonies, biometric characteristics may be associated with production traits, thus the study of correlations is extremely useful as a tool for colony selection process. The aim of this study was to estimate the correlations between biometric and productive parameters of Melipona quadrifasciata anthidioides. We analyzed 128 colonies, from 60 parental and two generations, F1 and F2. The following parameters were evaluated: queen and colony weight; number, length and width of brood disks; number, width, depth and volume of honey pots; number, width and depth of pollen pots; glossa size, and estimate of the population and honey production. The queen weight was correlated with the number of brood disks (0.23) and population (0.23), as well as the characteristic number of pollen pots is related to the length and width of brood disks and population (0.88, 0.54 and 0.52, respectively). The characteristic honey production is related to the number (0.93), width (0.50) and volume (0.47) of honey pots. The results showed that honey production is directly correlated with number, volume, width and depth of honey pots. On the other side, the population size was correlated with the number of brood disks and pollen pots.